Glycosylation at Asn254 Is Required for the Activation of the PDGF-C Protein - Hu, Wenjie; Zhang, Ruting; Chen, Wei; Lin, Dongyue; Wei, Kun; Li, Jiahui; Zhang, Bo; Li, Xuri; Tang, Zhongshu (Frontiers in Molecular Biosciences, 2021)
Platelet-derived growth factor C (PDGF-C) is a member of the PDGF/VEGF (vascular endothelial growth factor) family, which includes proteins that are well known for their mitogenic effects on multiple cell types. Glycosylation is one of the most important forms of posttranslational modification that has a significant impact on secreted and membrane proteins. Glycosylation has many well-characterized roles in facilitating protein processing and contributes to appropriate folding, conformation, distribution, and stability of proteins that are synthesized intracellularly in the endoplasmic reticulum (ER) and Golgi apparatus. Although the general process and functions of glycosylation are well documented, there are most likely others yet to be discovered, as the glycosylation of many potential substrates has not been characterized. In this study, we report that the PDGF-C protein is glycosylated at three sites, including Asn25, Asn55, and Asn254. However, we found that mutations at any of these sites do not affect the protein expression or secretion. Similarly, disruption of PDGF-C glycosylation had no impact on its progression through the ER and Golgi apparatus. However, the introduction of a mutation at Asn254 (N254 A) prevents the activation of full-length PDGF-C and its capacity for signaling via the PDGF receptor. Our findings reveal that glycosylation affects PDGF-C activation rather than the protein synthesis or processing. This study characterizes a crucial modification of the PDGF-C protein, and may shed new light on the process and function of glycosylation.